Hair and Claw Dehydroepiandrosterone Concentrations in Newborn Puppies Spontaneously Dead within 30 Days of Age - Jasmine Fusi; Maria Cristina Veronesi; Alberto Prandi; Tea Meloni; Massimo Faustini; Tanja Peric (Animals, 2022)
The latest intrauterine fetal developmental stage and the neonatal period represent the most challenging phases for mammalian offspring. Toward the term of pregnancy, during parturition, and after birth, the hypothalamic–pituitary–adrenal axis (HPA) is a key system regulating several physiologic processes, through the production of cortisol and dehydroepiandrosterone (DHEA). This study was aimed to assess DHEA concentrations in hair and claws of 126 spontaneously dead newborn puppies, classified as premature puppies (PRE-P), stillborn puppies (STILL-P) and puppies that died from the 1st to the 30th day of life (NEON-P). The possible influence of newborn sex, breed body size, and timing of death on DHEA concentrations in both matrices was evaluated. Claw DHEA concentrations were higher in the PRE-P group when compared to STILL-P and NEON-P puppies (p < 0.05), whilst no significant differences were found in hair for all the studied factors. The results confirm the hypothesis that higher amounts of DHEA are produced during the intrauterine life in dogs, also in puppies that will die soon after birth.